2023
DOI: 10.1371/journal.pone.0295644
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of human papillomavirus vaccine hesitancy among Lebanese parents

Ramia Zakhour,
Hani Tamim,
Farah Faytrouni
et al.

Abstract: Introduction Human papillomavirus (HPV) is the most common sexually transmitted infection. HPV is responsible for cancer of cervix uteri. Despite its safety and immunogenicity, HPV vaccine hesitancy is one of the most challenging topics that pediatricians face. Methods We aimed to describe the impact of knowledge, attitude, and practice towards vaccines in general, on practice related to HPV vaccination in Lebanon. A questionnaire addressed to parents of students (3–18 years of age) was distributed in 2 publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Research conducted in four countries in the MENA region revealed that a significant portion (60% to 78%) of parents whose children attend private and public schools are aware of cervical cancer. Despite receiving information about the HPV vaccine from healthcare providers, a staggering 95% of parents either had no knowledge of its causes or had never even heard of the HPV screening test [16]. Interestingly, only a small minority of parents, around 13%, suspected that the HPV vaccination was developed for commercial gain [17].…”
Section: Knowledge and Attitude Regarding Hpv Vaccine Acceptance Amon...mentioning
confidence: 99%
“…Research conducted in four countries in the MENA region revealed that a significant portion (60% to 78%) of parents whose children attend private and public schools are aware of cervical cancer. Despite receiving information about the HPV vaccine from healthcare providers, a staggering 95% of parents either had no knowledge of its causes or had never even heard of the HPV screening test [16]. Interestingly, only a small minority of parents, around 13%, suspected that the HPV vaccination was developed for commercial gain [17].…”
Section: Knowledge and Attitude Regarding Hpv Vaccine Acceptance Amon...mentioning
confidence: 99%